TARI BOKINUL SEBAGAI PENGUATAN DESTINASI KAWASAN WISATA JENAWI KABUPATEN KARANGANYAR - Karyono Karyono (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Artistic research activities (art creation) entitled “Bokinul dance as strengthening the distination of Jenawi regional tourism areas in Karanganyar regency”. Dance coaching is the service of artistic research (art cre-ation) as a form of collaboration to develop the creativity of performing arts and ethnic music, creating creativ-ity through local wisdom and originating from ancestral culture to capture the young generation together to preserve the surrounding cultural arts. Artistic research (art creation) aims (1). existing dance coaching, bokinul. (2) the development of dance forms in citing leads to character recognition training in dance movements, introduction of musical instruments and costumes to be worn. The approach method used in this activity is in the form of training and technical assistance in designing dance movements and accompanying music. Musi-cal instrument production training will be carried out in stages: costume-making training includes designing costumes, designing headdresses, designing accessories and finally activities, namely financial management training including calculation of production costs and selling prices, target achievements in this case for the community, these are design results dance and music design, products designed by musical instruments and costumes and the results of training in calculating production costs. While the output achievement target is a scientific report text presentation of the results of artistic research, in the form of performances and / or exhibitions.